The Effectiveness of Quarter Prone Position on Status Hemodynamics and Sleep Duration of Premature Infants - Mursiah Mursiah; Nyimas Heny Purwati; Anita Apriliawati; Awaliah Awaliah (Indonesian Journal of Global Health Research, 2024)
Prematurely born babies often face a range of complex issues such as body temperature instability, cardiovascular problems, fluctuations in blood pressure and heart rate, and respiratory disorders. Improper positioning exacerbates these challenges by compromising their underdeveloped homeostatic mechanisms, leading to physiological instability. Purpose: This study aimed to investigate the impact of the quarter-prone position on the hemodynamic status and sleep duration of premature infants.Methods: A quantitative approach was employed using a quasi-experimental research design with a pre-post control group. The study was conducted at one of urban hospitals in Indonesia over a one-month period from February to July 2023. Thirty-two participants were divided into intervention and control groups. Data analysis using univariate and bivariate analysis Independent T-Test.  Results: There are no statistically significant differences among the control and intervention groups (p-value > 0.005). that there is significant statistical difference among two group at post-test at all variables (p-value : 0.00) Discussion  The quarter-prone position, in conjunction with environmental factors like noise and lighting, influences the respiratory rate, heart rate, oxygen saturation, and sleep duration of premature infants. Nurses are encouraged to implement the quarter-prone position in caring for premature babies to enhance nursing quality and improve their overall quality of life. This approach is supported by its potential impact on the growth and developmental outcomes of premature infants in the long term.